Analisis Proses Penyelenggaraan Event: Studi Kasus Penyelenggaran “Grand Launching Mal Pelayanan Publik Kabupaten Gresik” oleh CV. Imagine Promosindo - Nugroho, Margaretta Andini; Meilia, Melania (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
One of the success factors in organizing an event or activity lies in the careful and considerate preparation process. This is the full responsibility of the event organizer as the party given the authority to organize the entire series of events. CV. Imagine Promosindo is one of the leading event organizers in Malang Regency with more than 10 years of experience in handling events, both at local and national levels. The event "Grand Launching of the Gresik Regency Public Service Mall" is one of the events handled by CV. Imagine Promosindo whose implementation was very successful even though it was held in the pandemic era. This is of course to the detailed preparation of the implementation process from the pre-event, on-event and post-event stages.